Efeito da comunicação persuasiva na intenção de uso do preservativo entre mulheres - Trevizolo, Karina Karla de Sá Gomes (2021)
Introduction: The use of condoms is still the best alternative to protect yourself from sexually transmitted infections, however, worldwide epidemics reveal the practice of unprotected sex and the increase in female vulnerability. Objective: To evaluate the effect of persuasive negative communication on the behavioral intention to use condoms among women in situations of social vulnerability, in the light of the Rational Action Theory. Method: Uncontrolled intervention study, before and after, with a quantitative approach, involving 46 women registered in an Integrated Family Health Unit in the city of João Pessoa, Paraíba. Data were analyzed using descriptive and inferential statistics (Shapiro-Wilk, Student's t, Spearman, Pearson's r, Stepwise and Wilcoxon). It was approved by the Research Ethics Committee of the Health Sciences Center of the Federal University of Paraíba, under protocols nº 0442/16 and CAAE nº 58597416.3.0000.5188. Results: Participants were predominantly young adults, with a partner, mixed race, Catholic and with low education. Behavioral intention was shown to be correlated with attitude prior to the intervention and, subsequently, with attitude and subjective norm. There was an influence of attitudinal and normative components on the intention to use condoms after persuasive communication, differing from the previous moment when only the attitude explained the intention. There was an increase in median intention scores after exposure to persuasive communication, although not significant. The comparison of data before and after the intervention made it possible to confirm its influence on the intention to use condoms. Conclusion: Persuasive negative communication, in audiovisual format, proved to be effective and innovative and can be applied to influence the intention to use condoms by women, supporting health professionals in the implementation of actions to prevent sexually transmitted infections.